2005
DOI: 10.1111/j.1478-3231.2005.01055.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical implications of HFE gene mutations (C282Y and H63D) in patients with chronic hepatitis B and C in Taiwan

Abstract: Almost all Taiwanese are C282Y wild type. H63D heterozygote and homozygote, occurring in less than 5% of the subjects, tended to be associated with the development of liver cirrhosis, irrespective of viral etiology. Screening for H63D mutation might be considered in patients with chronic viral hepatitis in Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
5
9
0
Order By: Relevance
“…Our data showed that the GNPAT variant plays a role in iron phenotype (increased serum iron levels at fasting and after supplementation) in healthy young Taiwanese women, a population that does not carry the HFE C282Y mutation. (5) Our findings suggest that GNPAT p.D519G is not an "HFE modifier," as proposed by McLaren et al, but is an independent player in hepcidin regulation. Further in vitro and human studies will be required to clarify the exact role of GNPAT in iron phenotype.…”
Section: To the Editorsupporting
confidence: 55%
“…Our data showed that the GNPAT variant plays a role in iron phenotype (increased serum iron levels at fasting and after supplementation) in healthy young Taiwanese women, a population that does not carry the HFE C282Y mutation. (5) Our findings suggest that GNPAT p.D519G is not an "HFE modifier," as proposed by McLaren et al, but is an independent player in hepcidin regulation. Further in vitro and human studies will be required to clarify the exact role of GNPAT in iron phenotype.…”
Section: To the Editorsupporting
confidence: 55%
“…In addition, the homozygous C282Y status was absent from individuals with chronic hepatitis as well as controls. Overall, these findings are in agreement with well documented studies from the Middle-East and eastern-Asia [Mah et al, 2005;Ghaziani et al, 2007] but differ from the report of Sendi et al [2005] showing that in Iranians patients, the frequency of major mutation C282Y in HFE gene with HBV infection is higher than control subjects (4% vs. 0%, P ¼ 0.02). However, it must be stressed that the latter study was performed on a limited number of patients (n ¼ 75).…”
Section: Discussionsupporting
confidence: 83%
“…In Morocco, available data were limited regarding HFE gene mutations [Ezzikouri et al, 2008]. In addition, only few studies have focused on the relationship between HFE mutations and the persistence of HBV infection [Mah et al, 2005;Sendi et al, 2005;Ghaziani et al, 2007]. The aim of the current study was to determine whether there is any difference between the frequencies of HFE mutations in patients with HBsAg and patients infected with hepatitis C virus (HCV), compared with an appropriate control group.…”
Section: Introductionmentioning
confidence: 95%
“…It may therefore be of interest to study whether patients with chronic hepatitis B or chronic heavy alcohol consumption who harbour the H63D mutaion are at greater risk of progression to cirrhosis than their counterparts who do not have this mutated allele. Few authors did not however find this relationship in their studies [21][22][23][24].…”
Section: Discussionmentioning
confidence: 77%
“…It is possible that mutation in this gene predisposes to development of cirrhosis in the presence of another cause of chronic inflammation of the liver such as chronic hepatitis B infection or alcohol. Several earlier studies have shown that H63D heterozygosity is associated with an increased risk for liver fibrosis and cirrhosis [19,21,22]. It may therefore be of interest to study whether patients with chronic hepatitis B or chronic heavy alcohol consumption who harbour the H63D mutaion are at greater risk of progression to cirrhosis than their counterparts who do not have this mutated allele.…”
Section: Discussionmentioning
confidence: 98%